Effect of H2O on metal–silicate partitioning of Ni, Co, V, Cr, Mn and Fe: Implications for the oxidation state of the Earth and Mars. (1st November 2016) - Clesi, V.; Bouhifd, M.A.; Bolfan-Casanova, N.; Manthilake, G.; Fabbrizio, A.; Andrault, D.
Abstract: This study investigates the metal–silicate partitioning of Ni, Co, V, Cr, Mn and Fe during core mantle differentiation of terrestrial planets under hydrous conditions. For this, we equilibrated a molten hydrous CI chondrite model composition with various Fe-rich alloys in the system Fe–C–Ni–Co–Si–S in a multi-anvil over a range of P, T, f O 2 and water content (5–20 GPa, 2073–2500 K, from 1 to 5 log units below the iron–wüstite (IW) buffer and for X H 2 O varying from 500 ppm to 1.5 wt%). By comparing the present experiments with the available data sets on dry systems, we observes that the effect of water on the partition coefficients of moderately siderophile elements is only moderate. For example, for iron we observed a decrease in the partition coefficient of Fe ( D met / sil Fe ) from 9.5 to 4.3, with increasing water content of the silicate melt, from 0 to 1.44 wt%, respectively. The evolution of metal–silicate partition coefficients of Ni, Co, V, Cr, Mn and Fe are modelled based on sets of empirical parameters. These empirical models are then used to refine the process of core segregation during accretion of Mars and the Earth. It appears that the likely presence of 3.5 wt% water on Mars during the core–mantle segregation could account for ∼74% of the FeO content of the Martian mantle. In contrast, water does not play such an important role for the Earth; only 4–6% of the FeO content of its mantle could be due to the water-induced Fe-oxidation, for a likely initial water concentration of 1.8 wt%. Thus, in order to reproduce the present-day FeO content of 8 wt% in the mantle, the Earth could initially have been accreted from a large fraction (between 85% and 90%) of reducing bodies (similar to EH chondrites), with 10–15% of the Earth's mass likely made of more oxidized components that introduced the major part of water and FeO to the Earth. This high proportion of enstatite chondrites in the original constitution of the Earth is consistent with the 17 O, 48 Ca, 50 Ti, 62 Ni and 90 Mo isotopic study by Dauphas et al. (2014). If we assume that the CI-chondrite was oxidized during accretion, its intrinsically high water content suggests a maximum initial water concentration in the range of 1.2–1.8 wt% for the Earth, and 2.5–3.5 wt% for Mars.